Overlap Between Autism Spectrum Disorders and Attention Deficit Hyperactivity Disorder: Searching for Distinctive/Common Clinical Features. Issue 3 (20th January 2015) - Craig, Francesco; Lamanna, Anna Linda; Margari, Francesco; Matera, Emilia; Simone, Marta; Margari, Lucia
<x xml:space="preserve">Abstract</x> Recent studies support several overlapping traits between autism spectrum disorders (ASD) and attention‐deficit/hyperactivity disorder (ADHD), assuming the existence of a combined phenotype. The aim of our study was to evaluate the common or distinctive clinical features between ASD and ADHD in order to identify possible different phenotypes that could have a clinical value. We enrolled 181 subjects divided into four diagnostic groups: ADHD group, ASD group, ASD+ADHD group (that met diagnostic criteria for both ASD and ADHD), and control group. Intelligent quotient (IQ), emotional and behavior problems, ADHD symptoms, ASD symptoms, and adaptive behaviors were investigated through the following test: Wechsler Intelligence Scale for Children, Wechsler Preschool and Primary Scale of Intelligence or Leiter International Performances Scale Revised, Child Behavior Checklist, Conners' Rating Scales‐Revised, SNAP‐IV Rating Scale, the Social Communication Questionnaire, Vineland Adaptive Behavior Scales. The ASD+ADHD group differs from ADHD or ASD in some domains such as lower IQ mean level and a higher autistic symptoms severity. However, the ASD+ADHD group shares inattention and hyperactivity deficit and some emotional and behavior problems with the ADHD group, while it shares adaptive behavior impairment with ASD group. These findings provide a new understanding of clinical manifestation of ASD+ADHD phenotype, they may also inform a novel treatment target. Autism Res2015, 8: 328–337. © 2015 International Society for Autism Research, Wiley Periodicals, Inc.